2014
DOI: 10.1152/ajprenal.00157.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prostasin interacts with the epithelial Na+channel and facilitates cleavage of the γ-subunit by a second protease

Abstract: During maturation, the α- and γ-subunits of the epithelial Na+ channel (ENaC) undergo proteolytic processing by furin. Cleavage of the γ-subunit by furin at the consensus site γRKRR143 and subsequent cleavage by a second protease at a distal site strongly activate the channel. For example, coexpression of prostasin with ENaC increases both channel function and cleavage at the γRKRK186 site. We generated a polyclonal antibody that recognizes the region 144-186 in the γ-subunit (anti-γ43) to determine whether pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 52 publications
(68 reference statements)
4
41
0
Order By: Relevance
“…Evidence for this comes from recent studies that employed an antibody raised against the γ subunit inhibitory tract. Sodium restriction lead to loss of the inhibitory tract from the C-terminal fragment, consistent with proteolytic removal of the inhibitory tract and channel activation 44 .…”
Section: Enac Activation In Nephrotic Syndromementioning
confidence: 63%
See 1 more Smart Citation
“…Evidence for this comes from recent studies that employed an antibody raised against the γ subunit inhibitory tract. Sodium restriction lead to loss of the inhibitory tract from the C-terminal fragment, consistent with proteolytic removal of the inhibitory tract and channel activation 44 .…”
Section: Enac Activation In Nephrotic Syndromementioning
confidence: 63%
“…Interestingly, prostasin does not require its proteolytic activity to activate ENaC 44,64 . Prostasin is present within a protein complex that contains ENaC, and recent work suggests that prostasin can recruit other proteases to this complex, resulting in channel cleavage and activation 44 . Svenningsen et al have suggested that prostasin facilitates the targeting of plasmin to ENaC at the plasma membrane 63 .…”
Section: Enac Activation In Nephrotic Syndromementioning
confidence: 99%
“…It is an emerging concept that serine proteases contribute to ENaC regulation by cleaving specific sites in the extracellular domains of the a-and g-subunits (6)(7)(8)(9)(10), resulting in the release of inhibitory peptides and activation of the channel (11)(12)(13). Proteolytic activation of ENaC by serine proteases as shown in native renal tissue (14) is enhanced by low-salt diet or aldosterone infusion (15) and might involve membrane-anchored prostasin (16) and/or tissue (urinary) kallikreins (17). Under pathophysiologic conditions of proteinuria, ENaC is thought to be aberrantly activated by plasmin that arises from filtered plasminogen and conversion by the tubular urokinase-type plasminogen activator (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Then, anti-V5 or anti-HA monoclonal ) antibodies were added to the samples (1:5,000 and 1:1,000 dilution, respectively). Our and other groups have demonstrated that non-ENaC bands could be detected in parental oocytes or oocytes expressing ENaC constructs without these artificial flags (Carattino et al, 2014;Ji, Zhao, Komissarov, Chang, Liu & Matthay, 2015;Passero, Mueller, Myerburg, Carattino, Hughey & Kleyman, 2012;Passero, Mueller, Rondon-Berrios, Tofovic, Hughey & Kleyman, 2008). Horseradish peroxidase-labelled secondary antibodies (Jackson Immunoresearch) were used (1:10,000).…”
Section: Biotinylation and Immunoblottingmentioning
confidence: 99%